Stock assessment of Lepturacanthus savala (Cuvier, 1829) along north-west sector of Mumbai coast in Arabian Sea - Rizvi, A F; Desmukh, S K; Chakraborty, S K (Indian Journal of Fisheries, 2016)
Population parameters of Lepturacanthus savala from the trawl and dol net catches from Mumbai waters were estimatedbased on length frequency data using FiSAT and ELEFAN. The length-weight relationship for pooled data waslog W = -7.9652 + 3.6117 log L (r = 0.962). The asymptotic length (L) and growth coefficient (K) were estimated to be 688mm, and 0.87 year-1, respectively. Based on these growth parameters, the instantaneous total mortality coefficient (Z) duringthe study period was estimated to be 4.15 year -1. The natural mortality coefficient (M) was 1.30. Hence fishing mortality (F)was 2.85 year -1 for L. savala. The estimated value for the exploitation ratio (E) was 0.68. The recruitment was continuouswith two peaks per year. The estimated size of L. savala at 50 percent probabilities of capture was 463 mm. An isoplethdiagram was obtained when E = 0.6 and Lc/L = 0.5.